2016
DOI: 10.1159/000452887
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics and Gender Differences in Prepubertal Children Treated with Growth Hormone in Europe, USA, and Japan: 25 Years' KIGS® Experience (1987-2012) and Review

Abstract: Background: Information about disease-specific and gender-associated differences over longer time of short children treated with recombinant human growth hormone is missing. Methods: We analyzed data at growth hormone (GH) start in prepubertal children diagnosed with idiopathic GH deficiency (IGHD), congenital GHD, acquired GHD, idiopathic short stature (ISS), and born small for gestational age (SGA) enrolled (1987-2012) in the Pfizer International Growth Study (KIGS®) from Europe, USA, and Japan. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 44 publications
12
39
0
4
Order By: Relevance
“…In the control, the statistical analysis revealed that they were divided into equal subgroups (50 % males and 50 % females). A similar result has also been observed by [19]. It has been noticed that more boys than girls are referred to endocrine clinics due to growth disturbances and that most cases of GHD among males are pituitary disorders;the function of the pituitary and particular the secretion of GH might be more susceptible in males than females.Also, short stature in girls is often not detected, or it is reported late [20].…”
Section: Results and Discussion Distribution Of The Studied Subjects supporting
confidence: 75%
“…In the control, the statistical analysis revealed that they were divided into equal subgroups (50 % males and 50 % females). A similar result has also been observed by [19]. It has been noticed that more boys than girls are referred to endocrine clinics due to growth disturbances and that most cases of GHD among males are pituitary disorders;the function of the pituitary and particular the secretion of GH might be more susceptible in males than females.Also, short stature in girls is often not detected, or it is reported late [20].…”
Section: Results and Discussion Distribution Of The Studied Subjects supporting
confidence: 75%
“…At the start of rhGH, girls with NS tend to be younger and smaller, which may be the results of a bias of inclusion also suspected in other growth disorders treated with GH [33]. The observation that the difference in height SDS between the sexes is significant only when normal references are used, but not if NS specific references are applied, is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Although the GH response in ISS is well-known, responsiveness varies among individuals diagnosed with ISS. There have been many attempts at developing GH prediction models calculated based on the available information (Wikland et al 2000;Ranke et al 2017). Bakker et al (2008) evaluated GH response among good responders and poor responders according to HV and Δheight SDS using data from the National Cooperative Growth Study.…”
Section: Discussionmentioning
confidence: 99%